The Gamut of e-commerce: between online fraud and trust towards technology among generation Y / Zuhal Hussein - Hussein, Zuhal (IAEME Publication, 2019)
At present, generation Y represents the most population in the world and their acceptance either as consumers, users or clients plays a significant and important role in making the business world doomed or brighter. Therefore, their behaviour plays the most important role in ensuring e-commerce does well and making the online business industry grow tremendously. Yet, little is known about the intention among generation Y with regards to e-commerce. This study aims to identify the online fraud and trust towards the technology influencing the intention to use e-commerce among generation Y. A total of one hundred and twenty respondents of generation Y were recruited in this study through convenience sampling at Kota Bharu city. This quantitative study using survey as a method of data collection and a questionnaire was distributed to the respondents to fill. The respondents were asked for consent before proceeding with the survey, in order to ensure that the ethical consideration was taken into account while conducting the study. Data were analysed using Pearson correlation and multiple regression analysis. Findings revealed that trust and online fraud had a positive and significant relationship with consumer intention, and they were significantly affecting the intention of generation Y. This study would suggest that the online business companies and e-commerce technologies should consider focusing on these variables in the development and implementation of a strategy to attract and retain buyers in the future.